Stratification and environmental dissimilarity in corn genotypes at Tocantins, with different fertilizations and seasons - de Carvalho, Edmar Vinícius; Afférri, Flávio Sérgio; Peluzio, Joênes Muci; Rotili, Eliane Aparecida; Dotto, Michel Antônio; dos Santos, Weder Ferreira (Comunicata Scientiae, 2013)
The aim was to evaluate the stratification and environmental dissimilarity effect in corn genotypes,in relation grain yield and green weight of plant, at Tocantins, they were used the fertilizationmanagement and season as factors of distinction the environments. They were conducted eightexperiments with experimental design completely randomized blocks, with 16 genotypes and tworeplications, each one. The green weight of plant was evaluated at the flour grain stage and, thegrain yield, after physiological maturation. The environmental stratification was done by Lin (1982)method. The environmental dissimilarity was done by Cruz & Castoldi (1991) method, and it wasobtained the simple e complex fraction of GxE interaction, in addition was estimated the Pearsoncorrelation between the pair of environments. The complex fraction was represented, for bothcharacteristics, 90% of GxE interaction. The fertilization management and the season were effectiveto provide distinction conditions of genotype development.